2013
DOI: 10.1016/j.ultrasmedbio.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thyroid Cancer in Mouse Models Using High-Frequency Quantitative Ultrasound Techniques

Abstract: Currently, the evaluation of thyroid cancer relies on the use of fine needle aspiration biopsy as non-invasive imaging methods do not provide sufficient levels of accuracy for the diagnosis of this disease. In this study, the potential of quantitative ultrasound methods for characterizing thyroid tissues was studied using a rodent model ex vivo. A high-frequency ultrasonic scanning system (40 MHz) was used to scan thyroids extracted from mice that had spontaneously developed thyroid lesions (cancerous or benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…The estimated mean values are consistent with values obtained previously by an insertion loss method which obtained a mean attenuation value of the sample of 1.19 ± 0.26 dB/cm-MHz [4] in mice thyroids. These values are also consistent with reports of attenuation in human thyroids [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The estimated mean values are consistent with values obtained previously by an insertion loss method which obtained a mean attenuation value of the sample of 1.19 ± 0.26 dB/cm-MHz [4] in mice thyroids. These values are also consistent with reports of attenuation in human thyroids [11].…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, the FV-PTC and PTC groups in mouse models were identified using ESD and EAC [4,10]. However, these estimators could not differentiate the C-cell adenomas from the normal thyroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-frequency single-element ultrasonic scanning system was used to scan thyroids extracted from mice that had spontaneously developed thyroid lesions (cancerous or benign) [89]. Four sets of mice were acquired having different predispositions to developing thyroid anomalies.…”
Section: Successful Applications Of Quantitative Ultrasoundmentioning
confidence: 99%
“…Certain chemical and molecular changes in the nucleus and cell morphology are seen in papillary thyroid carcinoma variants, and these changes have been characterized by scattering properties. [12][13][14] In a population-based study by Smith-Bindman et al, 15 microcalcifications were associated with 38.2% of malignant nodules and 5.4% of benign nodules. Models for classifying microcalcifications as elastic scatterers under ultrasound have been studied previously.…”
Section: Introductionmentioning
confidence: 96%